C2-substituted aromatic cytokinin sugar conjugates delay the onset of senescence by maintaining the activity of the photosynthetic apparatus - Vylíčilová, Hana; Husičková, Alexandra; Spíchal, Lukáš; Srovnal, Josef; Doležal, Karel; Plíhal, Ondřej; Plíhalová, Lucie (Phytochemistry, 2016)
Cytokinins are plant hormones with biological functions ranging from coordination of plant growth and development to the regulation of senescence. A series of 2-chloro-N(6)-(halogenobenzylamino)purine ribosides was prepared and tested for cytokinin activity in detached wheat leaf senescence, tobacco callus and Amaranthus bioassays. The synthetic compounds showed significant activity, especially in delaying senescence in detached wheat leaves. They were also tested in bacterial receptor bioassays using both monocot and dicot members of the cytokinin receptor family. Most of the derivatives did not trigger cytokinin signaling via the AHK3 and AHK4 receptors from Arabidopsis thaliana in the bacterial assay, but some of them specifically activated the ZmHK1 receptor from Zea mays and were also more active than the aromatic cytokinin BAP in an ARR5::GUS cytokinin bioassay using transgenic Arabidopsis plants. Whole transcript expression analysis was performed using an Arabidopsis model to gather information about the reprogramming of gene transcription when senescent leaves were treated with selected C2-substituted aromatic cytokinin ribosides. Genome-wide expression profiling revealed that the synthetic halogenated derivatives induced the expression of genes related to cytokinin signaling and metabolism. They also prompted both up- and down-regulation of a unique combination of genes coding for components of the photosystem II (PSII) reaction center, light-harvesting complex II (LHCII), and the oxygen-evolving complex, as well as several stress factors responsible for regulating photosynthesis and chlorophyll degradation. Chlorophyll content and fluorescence analyses demonstrated that treatment with the halogenated derivatives increased the efficiency of PSII photochemistry and the abundance of LHCII relative to DMSO- and BAP-treated controls. These findings demonstrate that it is possible to manipulate and fine-tune leaf longevity using synthetic aromatic cytokinin analogs.
Keywords: ribonukleosidy; Purine Nucleosides; Arabidopsis; vztahy mezi strukturou a aktivitou; Plant Development; Photosystem; Nicotiana; stárnutí; Cytokinin activity; Synthesis; listy rostlin; Structure-Activity Relationship; metabolismus sacharidů; Ribosides; pšenice; Amaranthus; tabák; Senescence delay; Photosynthetic Reaction Center Complex Proteins; Carbohydrate Metabolism; Aging; vývoj rostlin; Plant Leaves; amarant; Photosynthesis; Gene expression; fotosyntetická reakční centra (proteinové komplexy); Triticum; Cytokinins; cytokininy; Aromatic cytokinin; Ribonucleosides; purinové nukleosidy